2018
DOI: 10.1021/acs.inorgchem.7b01894
|View full text |Cite
|
Sign up to set email alerts
|

Redox Potentials for Tetraplatin, Satraplatin, Its Derivatives, and Ascorbic Acid: A Computational Study

Abstract: Redox potentials of the Pt(IV) complexes, such as satraplatin, tetraplatin, and several others, are determined at the density functional theory (DFT) level (with B3LYP, ω-B97XD, PBE1PBE, TPSSTPSS, M06-L, M11-L, and MN12-L functionals) and compared with post-Hartree-Fock methods MP2 and CCSD(T). Calculations are performed in water solution employing an implicit solvation model. The impact of replacement of a chloro ligand by a water molecule (hydration in the equatorial plane of the complexes) is also explored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Since the electron transfer is accompanied by the release of the two axial ligands, the measured peak potentials do not necessarily correlate with the rate of the reduction process that depends both on the rate of the electron transfer and on strength of the bonds between the ligands and the metal center. Theoretical procedures for the elucidation of the reduction mechanism and calculation of redox potential have been proposed. , Baik and co-workers have demonstrated that reduction occurs in two steps. The first step involves one electron transfer accompanied by the formation of a six-coordinate Pt­(III) complex and, being less exergonic than the second one, determines the magnitude of the redox potential as it has been confirmed by computations. , …”
Section: Introductionmentioning
confidence: 99%
“…Since the electron transfer is accompanied by the release of the two axial ligands, the measured peak potentials do not necessarily correlate with the rate of the reduction process that depends both on the rate of the electron transfer and on strength of the bonds between the ligands and the metal center. Theoretical procedures for the elucidation of the reduction mechanism and calculation of redox potential have been proposed. , Baik and co-workers have demonstrated that reduction occurs in two steps. The first step involves one electron transfer accompanied by the formation of a six-coordinate Pt­(III) complex and, being less exergonic than the second one, determines the magnitude of the redox potential as it has been confirmed by computations. , …”
Section: Introductionmentioning
confidence: 99%
“…From the data collected in the Results section (plus the available data corresponding to the acidity and redox characteristics at pH=7.0 of the free biomolecules used in this study and collected in Table 5), it is clear that the observed lack of reactivity of the methionine molecules with the PtIV complexes could not be associated with the reduction potential. Methionine is, in fact, the most readily oxidised of the thiol derivatives used [43], which indicates, as stated before, that the thermodynamic oxidation of these biomolecules does not correspond to the processes by which the reduction of PtIV complexes are reduced [16][17][18]44]. Neither the formation of SeS bonds nor sulfoxide formation are relevant for the reaction observed, the process being already described as a reductive elimination S-Cl reaction occurring on the PtIV starting material (Scheme 2) [17].…”
Section: Discussionmentioning
confidence: 85%
“…9 Indeed, the Pt(IV) complexes lose the two axial ligands during the reduction reaction since the two accepted electrons enter the d z2 orbital (LUMO), which destabilizes the ligands in axial positions. 146 In most cases this statement is confirmed, however, some rearrangements resulting in the formation of different Pt(II) metabolites have been reported. 119,147,148 Several attempts to rationalize the behavior of these Pt(IV) compounds have been made but probably further data will be necessary to draw the whole picture.…”
Section: Reduction Of Pt(iv) Prodrugsmentioning
confidence: 89%